Strategic planning, execution, and measurement (SPEM) : a powerful tool for CEOs - Jākhoṭiyā, Girīśa Pa (Taylor & Francis, 2013)
Although there are countless books available on strategic management, there are few, if any, that supply practical coverage of strategic planning, execution, and measurement-until now. Considering the entire value chain, this book covers the complete process of strategic planning, execution, and measurement. Based on three decades of field-tested experience, Strategic Planning, Execution, and Measurement (SPEM): A Powerful Tool for CEOs provides both a consultant's view and an entrepreneurial approach to strategic planning, execution, and measurement. Walking you through the process, it begins.